2017
DOI: 10.1021/acsami.7b04484
|View full text |Cite
|
Sign up to set email alerts
|

Visible Thermochromism in Vanadium Pentoxide Coatings

Abstract: OATAO is an open access repository that collects the work of Toulouse researchers and makes it freely available over the web where possible. ABSTRACT: Although di-vanadium pentoxide (V 2 O 5 ) has been a candidate of extensive research for over half a century, its intrinsic thermochromism has not been reported so far. Films of V 2 O 5 grown on silicon, glass, and metal substrates by metal organic chemical vapor deposition in this study exhibit a thermally induced perceptible color change from bright yellow to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
48
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 46 publications
(50 citation statements)
references
References 43 publications
1
48
1
Order By: Relevance
“…We find that the introduction of Sn 2+ in the reaction is pivotal for modulating T trans by over 100 °C, which is quite remarkable considering that T trans is fixed in most thermochromic systems as it is generally tied to a temperature specific phase transition, molecular structure rearrangement, or a charge‐transfer reaction . Larger amounts of Sn 2+ results in a higher temperature needed to effect net NW growth, and a noticeably faster rate of NW dissolution that is marked by the accelerated fading of the intense brown color to pale yellow.…”
mentioning
confidence: 77%
See 1 more Smart Citation
“…We find that the introduction of Sn 2+ in the reaction is pivotal for modulating T trans by over 100 °C, which is quite remarkable considering that T trans is fixed in most thermochromic systems as it is generally tied to a temperature specific phase transition, molecular structure rearrangement, or a charge‐transfer reaction . Larger amounts of Sn 2+ results in a higher temperature needed to effect net NW growth, and a noticeably faster rate of NW dissolution that is marked by the accelerated fading of the intense brown color to pale yellow.…”
mentioning
confidence: 77%
“…The origin of these reversible temperature‐dependent color changes is usually attributed to a shift in the chemical equilibrium between molecular isomers, a phase transition between inorganic solids, or a change in the crystalline phases of liquid crystals . To date, many thermochromic materials have been reported and commercialized, such as leuco dyes, thermotropic liquid crystals, titanium and vanadium oxides, and peptide‐based polydiacetylene . Among these examples, the liquid‐based leuco dyes and liquid crystals are unique as they can easily be made to fill various shaped voids, can be deposited onto virtually any substrate, and are straightforward to scale‐up in terms of production.…”
mentioning
confidence: 99%
“…Thin films of vanadium oxide were deposited on silicon substrates by Direct Liquid Injection (DLI) Metal Organic Chemical Vapor Deposition (MOCVD), the details of which are reported elsewhere [1] , [2] . Argon was used as the carrier gas at a flow rate of 50 sccm while the chamber pressure was adjusted to 10 mbar.…”
Section: Experimental Design Materials and Methodsmentioning
confidence: 99%
“…Photographic evidence is also shown to provide the reader a clear visual description of the color change that occurs during thermochromic process. Detailed study and analysis regarding this data can be found in Kumar et al (2017, in press) [1 , 2] .…”
mentioning
confidence: 99%
“…The thermochromic behavior of ABIF can be classified as irreversible. It is known that irreversible thermochromism is useful in situations in which it is necessary to keep a record of the change in temperature even after the temperature stimulus has been withdrawn . Such inorganic NLO crystals with the effects of both SHG and thermochromism have rarely been reported and may be useful for the study of the functional coupling of NLO and thermochromism.…”
Section: Figurementioning
confidence: 99%